Students’ Perceptions on Wordup Application to Enhance English Vocabulary: Persepsi Mahasiswa terhadap Aplikasi Wordup untuk Meningkatkan Kosakata Bahasa Inggris - Ardina Khoirunnisa Hasibuan; Maryati Salmiah (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Vocabulary mastery is a key challenge for junior high school students, as they often face difficulties in remembering and applying new words effectively. Purpose: This study aims to explore students’ perceptions of using the WordUp application to enhance English vocabulary learning. Method: A qualitative case study design was applied with 11 junior high school students aged 14-15. Data were collected through open-ended questionnaires and semi-structured interviews, then analyzed thematically using Braun and Clarke’s (2006) six-phase framework. The instruments included ten descriptive questions and follow-up interviews conducted via online sessions. The purposive sampling technique was used with the criterion of active involvement in English learning. Results and Discussion: The analysis revealed eight key themes. Students reported that WordUp supported vocabulary comprehension and retention through contextual examples, repetition, and pronunciation features. Interactive tools such as quizzes, daily words, and favorite lists increased engagement, while the app’s design and gamification elements enhanced motivation. WordUp also contributed to students’ confidence in applying vocabulary in academic tasks and informal communication. However, limitations were identified, including internet dependency and the absence of writing practice. Conclusions and Implications: WordUp is perceived as an effective and flexible vocabulary learning tool that supports autonomous learning and student motivation. The findings highlight the importance of integrating mobile applications into formal and informal English instruction to strengthen vocabulary development.